Facial palsy after administration of immune checkpoint inhibitors: case report, literature review and clinical care management - Mezni, Essia; Corazza, Giovanni; Mari, Roxane; Coze, Stephanie; Charrier, Nathalie; Chanez, Brice; Chretien, Anne Sophie; Rochigneux, Philippe (Frontiers in Immunology, 2024)
Neurological immune-related adverse events (irAEs) due to immune checkpoint inhibitors (ICI) are rare complications of immunotherapy, particularly dreadful for patients and clinical teams. Indeed, neurological irAEs are potentially severe and their diagnosis require prompt recognition and treatment. Additionally, the spectrum of neurological irAEs is broad, affecting either neuromuscular junction, peripheral or central nervous system. Here, we described the case of a 55-year man with metastatic melanoma, facing a brutal right peripheral cerebral palsy after his third ipilimumab/nivolumab infusion. After the case presentation, we reviewed the literature about this rare complication of immunotherapy, and described its diagnosis work-up and clinical management.